Sociological Review of Women Participation in Social Movements of Nepal - Dahal, Radhika Devi (Interdisciplinary Journal of Management and Social Sciences, 2024)
This article applies social structural approach to analyze women’s involvement in social and political movements. It studies feminist movement of the world, and draws conclusion on the history and contemporary state of women as participants of movement sin Nepal. It reviews some theoretical articles written by foreign scholars by giving equal emphasis to Nepali writers’ articles to review the evolution of women participation in movements in Nepal. Throughout the paper, feminist movement in common and issues of women exclusion in particular are discussed. Women issues or the feminist movements are often taken as lightly, but the paper believes that women participation in social and political movements of Nepal is attached more to class component than the purely qualitative component like social exclusion. To be specific, middle-class women in Nepal are the pioneers of women’s rights movement, and have contributed a lot to ensure women rights both in legal and political areas. Rights and privileges given to women both constitutionally and politico-culturally, basically from the 1990s in Nepal, and the benefit women have received in the fields of education, health, politics, employment, marriage, property, etc. are the results of middle-class women’s actively leading role in political movements.